Synergetic Sensorless Speed Decoupled Control of Induction Motor using an Adaptive Sliding Mode Observer - Aissaoui, Bouchra; Kouzi, Katia (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2023)
This articles proposes for making the development of the control of induction motor in first we start with the modeling of this motor then we find that there is a non-linearity in its model After the simulation which make it difficult to control so we go to the transformation of park. with MATLAB we observe that there is a coupling between the torque and the flux, to avoid this problem a victor control method with conventional PI is proposed. After the simulation we notice that the PI classic is not ideal in the case of disturbances, so we use the fuzzy regulator which gives us perfect results compared to the PI regulator. After that we do the synergetic control to improve our system, and we conclude by the adaptive observer by sliding mode which gives us ideal results improve the robustness of our full observer where there is a parameter variation and it has a good pursuit to the real parameter.
Option : Automatic and systems